Relationship of training and development, political interference, technological advancement and, organizational support: a study of Punjab Police (Pakistan) - Shahzad, Arfan; Sri Ramalu, Subramaniam (College of Law, Government and International Studies, Universiti Utara Malaysia, 2017)
This study intended to examine the relationship of political interference, technological advancement and training and development with the moderating effect of organizational support on the performance of Punjab police Pakistan. Besides, this study used the quantitative research approach for gathering of data. In the lieu of this, 159 survey questionnaires were collected from SHOs (Station House Officers) of Punjab police (Pakistan). Moreover, PLS-SEM and SPSS techniques were applied to scrutinize the data. The findings of the present study showed the significant positive effect of technological advancement and training & development on the performance of Punjab police, meanwhile, on the other hand, the political interference negatively affecting the performance of Punjab police (Pakistan). Also, the findings of the study exhibited the significant moderating effect of organizational support in the instance of technological advancement and training & development but in the case of political interference moderation did not play any role.